Electrochemical Activity of Nitrogen‐Containing Groups in Organic Electrode Materials and Related Improvement Strategies. Issue 7 (12th January 2021) - Yu, Qianchuan; Xue, Zhihuan; Li, Meichen; Qiu, Peimeng; Li, Changgang; Wang, Shengping; Yu, Jingxian; Nara, Hiroki; Na, Jongbeom; Yamauchi, Yusuke
Abstract: In recent years, due to their structural diversity, adjustability, versatility, and excellent electrochemical properties, organic compounds with nitrogen‐containing groups (OCNs) have become some of the most promising organic electrode materials. The nitrogen‐containing groups acting as electrochemical active sites include carbon–nitrogen groups, nitrogen–nitrogen groups, nitrogen–oxygen groups in OCNs, and nitrogen‐containing groups in covalent organic frameworks. The molecular structure regulation of OCNs with nitrogen‐containing groups acting as electrochemical active centers can suppress dissolution in electrolytes, increase electronic conductivity, and improve the kinetics of redox reactions. The kinetics behavior and electrochemical characteristics of OCN electrode materials in alkali metal rechargeable batteries with organic electrolytes are reviewed, and the related relationships between the structure and electrochemical properties of OCNs are the core of this review. Herein, the electrochemical reaction mechanisms and the strategies to improve the electrochemical activity of nitrogen‐containing groups in OCNs are clarified, and the conjugate molecular structure of OCNs is shown to be an important direction for improvement. These results will have implications for research on electrode materials and provide more choices for rechargeable batteries. Moreover, this work will guide the study of more efficient OCNs that can be used as electrode materials. Abstract : Organic compounds with nitrogen‐containing groups (OCNs) have gained increasing attention as next‐generation energy storage materials. This review summarizes the recent advances in this fast‐growing field, with a particular focuse on the electrochemical reaction mechanism and kinetics of the active OCNs (sites) and structure‐property relationships. New strategies are proposed to further improve their insolubility, electronic conductivity, and electrochemical performance.